Performance Evaluation of Multi-Cloud Failover Using Domain Name System - Zaelani, Cahya; Muhammad Suranegara, Galura (Journal of Applied Informatics and Computing, 2026)
This research implements and analyzes a multi-cloud failover system using DNS failover via AWS Route53 and Nginx reverse proxy load balancers on Google Cloud (primary) and Herza Cloud (backup), with AWS EC2 as shared backend web servers. An Ubuntu control node orchestrates deployments across these providers, enabling automatic traffic rerouting from the primary to secondary load balancer upon failure detection via health checks. Performance testing employed wrk benchmarking (4 threads, 250 connections, 300s) and Python monitoring scripts under baseline and failover scenarios with DNS TTLs of 30s, 60s, and 120s. Baseline yielded 2,291.81 req/s throughput, 108.42ms average latency, and 231.15ms p99 latency. Failover results showed TTL 30s optimal for reliability (152.65s downtime, 48.62% failed requests, 30.53s average recovery), outperforming TTL 60s (243.92s downtime, 83.48% failures due to health check mismatch) and TTL 120s (186.88s downtime) and TTL 30s is recommended for high availability in low-budget SMEs, balancing reduced downtime against DNS overhead. However, this approach is limited to small-scale infrastructure.